MiR‐218 affects the ECM composition and cell biomechanical properties of glioblastoma cells. Issue 14 (15th June 2022) - Grabowska, Małgorzata; Kuczyński, Konrad; Piwecka, Monika; Rabiasz, Alicja; Zemła, Joanna; Głodowicz, Paweł; Wawrzyniak, Dariusz; Lekka, Małgorzata; Rolle, Katarzyna
Abstract: Glioblastoma (GBM) is the most common malignant brain tumour. GBM cells have the ability to infiltrate into the surrounding brain tissue, which results in a significant decrease in the patient's survival rate. Infiltration is a consequence of the low adhesion and high migration of the tumour cells, two features being associated with the highly remodelled extracellular matrix (ECM). In this study, we report that ECM composition is partially regulated at the post‐transcriptional level by miRNA. Particularly, we show that miR‐218, a well‐known miRNA suppressor, is involved in the direct regulation of ECM components, tenascin‐C (TN‐C) and syndecan‐2 (SDC‐2). We demonstrated that the overexpression of miR‐218 reduces the mRNA and protein expression levels of TN‐C and SDC‐2, and subsequently influences biomechanical properties of GBM cells. Atomic force microscopy (AFM) and real‐time migration analysis revealed that miR‐218 overexpression impairs the migration potential and enhances the adhesive properties of cells. AFM analysis followed by F‐actin staining demonstrated that the expression level of miR‐218 has an impact on cell stiffness and cytoskeletal reorganization. Global gene expression analysis showed deregulation of a number of genes involved in tumour cell motility and adhesion or ECM remodelling upon miR‐218 treatment, suggesting further indirect interactions between the cells and ECM. The results demonstrated a direct impact of miR‐218 reduction in GBM tumours on the qualitative ECM content, leading to changes in the rigidity of the ECM and GBM cells being conducive to increased invasiveness of GBM.